Developing Santri’s Soft Skills through Engaging Extracurricular Activities at Pondok Pesantren - Aminullah Aminullah; Uryatul Hikmah; Yusril Ihza Saputra; Hafidatun Nabila; Moh. Holidi; Hefniy Hefniy (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the development of students' soft skills through extracurricular activities at the An-Nashiriyah Islamic Boarding School, Bawean Gresik Island, especially in the aspects of communication, confidence, leadership, teamwork, discipline, and responsibility. The research method used is qualitative with a case study approach and grounded research. Data was collected through observation, in-depth interviews, and documentation studies, then analyzed through the stages of data condensation, data presentation, and verification with content and interpretive analysis techniques. The results of the study show that extracurricular activities play a significant role in shaping students' soft skills through the process of habituation, active involvement, and direct experience in organizational activities, committees, and routine exercises. Strengthening communication skills and self-confidence occurs through speech and discussion activities, while leadership and teamwork are formed through student organizations. Discipline and responsibility develop through obedience to rules and the execution of duties. The implications of this study emphasize the importance of managing structured and sustainable extracurricular activities as an effective strategy in developing students' soft skills, so as to support the formation of Islamic boarding school graduates who are socially competent and adaptive to the demands of modern life